To evaluate the role of Vitamin C in reducing the resuscitation fluid volume requirement in burned patients - Bharti Tanwar; Dipan Uppal; Rajinder K Mittal; Sandeep Kaushal; Ramneesh Garg; Sheerin Shah; Sanjeev Uppal (Wolters Kluwer Medknow Publications, 2018)
Introduction: Free radicals released after burn injury lead to vascular endothelial injury and contribute to capillary leakage which in turn leads to burn edema. Antioxidant therapy (Vitamin C), to scavenge these free radicals, is suggested to limit endothelial injury and hence limit capillary leakage which in turn leads to reduction in fluid requirement to resuscitate the burn patient. Materials and Methods: This was a prospective, randomized study of 30 burn patients with 20%-60% burns. Fifteen patients were taken in each group. Group A patients were treated with only RL and Group B were treated with RL and adjuvant Vitamin C infusion. Fluid requirement, urine output, fluid balance, body weight gain, Vitamin C, and malondialdehyde (MDA) levels were noted. The two groups were then compared. Results: Fluid requirement in Group A was 3.74 ± 0.57 ml/kg/% of burns and in Group B was 2.46 ± 0.54 ml/kg/% of burns. Urine output was 1.05 ± 0.28 ml/kg/h in Group A, and in Group B, it was 1.42 ± 0.39 ml/kg/h. Fluid retention and body weight gain were lower in Group B. MDA levels were significantly lower at 36 h in Group B. Conclusion: Vitamin C, when given as adjuvant therapy in burns, decreases fluid requirement and lowers the MDA levels showing antioxidant effect of Vitamin C.